Pokdakan Mino Ngremboko's Business Recovery Strategy: Resilience Analysis and Supply Chain Integration - Sylvano Akbariansyah Cahyacipta; Jangkung Handoyo Mulyo; Any Suryantini (Jurnal Perikanan Universitas Gadjah Mada, 2023)
Mino Ngremboko Fish Cultivator Group (or Pokdakan Mino Ngremboko) is the pioneer of fish cultivation, which has been developing rapidly since its establishment in April 1987 until now (the beginning of 2021). Corona Virus Disease (Covid-19) pandemic has been attacking Indonesia violently (since March 2, 2020), disrupting the supply chain of the fish cultivation business. The negative impact is a decline in revenue significantly. Mino Ngremboko Cultivator, for instance, has been affected by the pandemic with an average revenue (demand) loss of 50-70 percent. In addition, business resilience becomes very crucial which comprises business continuity that represents the ability of businesses to rapidly adapt and respond to the pandemic crisis (EIB, IBRD, 2022). The objective of the study is to assess the resilience and supply chain integration of the Mino Ngremboko Cultivator in facing the Covid-19 pandemic and beyond. Method this study uses the inductive-qualitative approach through a case study of Mino Ngremboko Cultivator. Data was collected through unstructured interviews and observation from NovemberÂ  2020 to MarchÂ  2021. The study results provide three constructive insights, especially for managing Mino Ngremboko Cultivator and Fish Cultivator Group in general for sustaining their businesses. (1) Supply chain resilience is relatively good, which was shown by the average of productivity 1,10 from March 2019 to March 2021; (2) supply chain integration of fish cultivation business was not optimally implemented yet, and (3) Pokdakan Mino Ngremboko's business recovery strategy to optimise the practices of supply chain integration based on the digital marketing as well as downstream and commercialisation the output of fish cultivation. These recovery strategies require the support of improving organisation capability and stakeholder alignment to contribute to sustainable development (benefits for the social and ecological environment) in 2022 and beyond.